CONSUMPTION PATTERN OF CONVENIENCE FOODS AMONG CONSUMERS IN KANNUR DISTRICT, KERALA: CONSUMPTION PATTERN OF CONVENIENCE FOOD AMONG CONSUMERS - TEENA THOMAS; ANU JOSEPH (The Journal of Research ANGRAU, 2026)
The consumption of convenience foods has been steadily increasing in recent years, makingit important to understand the factors driving this trend. The present study examines the socioeconomicfactors influencing convenience food consumption patterns among consumers in Kannurdistrict, Kerala, India. A total of 175 respondents, aged 18 to 75 years, including both males andfemales, representing various socio-economic strata, participated in the survey. The results ofthe study reveal that convenience food consumption was predominantly higher among individualsof the younger age group (35%), those residing in rural areas (33%) and people with highereducational qualifications (24%). Expenditure on convenience foods constitute less than 10% oftheir monthly income. The study also identifies social media advertisements and recommendationsfrom relatives and friends as significant factors influencing the purchase of convenience foods.The frequent purchase of items such as biscuits and bread was a more common consumableamong the subjects. This study revealed an increase in the consumption of ready-to-eat andready-to-cook products in rural areas compared to other regions.